2003
DOI: 10.1057/palgrave.pm.5940250
|View full text |Cite
|
Sign up to set email alerts
|

Financial system requirements for successful pension reform

Abstract: This paper examines the financial system prerequisites needed for the successful delivery of funded private pensions. In particular, it examines the financial instruments and investment strategies required during both the accumulation and decumulation stages. It does so within the context of a specific developed economy with a mature pension system, namely the United Kingdom. The lessons learned can help to inform the debate in developing countries that are in the process of undertaking pension reform.JEL: E21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This is particularly true for local pension fund equity allocations and insurance companies. Opening up the opportunities to foreign securities of mid and long range maturities helps insurance companies and pension funds to resolve a problem facing many of them, that is, the mismatch between the duration of their assets and liabilities across the emerging markets (Blake, 2003;Briys and de Varenne, 1996;Kimmis et al, 2002). Another major driving force behind this policy device is the imbalanced, faster growth rate of assets under management compared to the volume and variety of available local securities.…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly true for local pension fund equity allocations and insurance companies. Opening up the opportunities to foreign securities of mid and long range maturities helps insurance companies and pension funds to resolve a problem facing many of them, that is, the mismatch between the duration of their assets and liabilities across the emerging markets (Blake, 2003;Briys and de Varenne, 1996;Kimmis et al, 2002). Another major driving force behind this policy device is the imbalanced, faster growth rate of assets under management compared to the volume and variety of available local securities.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, DC schemes benefit from higher levels of portability and flexibility than DB schemes, which may make them more suitable to contemporary patterns of employment and particularly attractive to young employees (Clark and Strauss, 2008). Blake (2003) found that, by changing jobs six times during a person's working life, between 25 and 30% of the full service DB pension is likely to be lost. This is particularly problematic given that many women have complex work histories, including career breaks and shorter employment tenures.…”
Section: Women Employment and Private Pensionsmentioning
confidence: 99%
“…As a result, pension fund trustees may have become wary of investing in emerging markets for fear of facing substantial short‐term losses (Kimmis et al. , 2002, and Blake, 2003). In the United States, fear of litigation in case of serious short‐term underperformance increases the risk perception of pension fund managers.…”
Section: Pension Funds In Developed Countriesmentioning
confidence: 99%
“…Perfect asset‐liability matching both in size and volatility is not feasible. However, investments in domestic assets match better domestic liabilities than investments in foreign securities (Blake, 1999 and 2003, and Davis and Steil, 2001).…”
Section: Pension Funds In Developed Countriesmentioning
confidence: 99%
See 1 more Smart Citation